Hoax from the Perspective of Islamic Legal Thought: Reactivating Qat‘i-Zanni in the Post-Truth Era - Prihantoro, Hijrian Angga; Mustafid, Fuad (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
The widespread dissemination of news in the Post-Truth era, relying on content and the speed of sharing without critically questioning its source or the transmitter, has an impact on subjective claims of truth that are prone to causing conflicts. This article discusses the issue of the spread of hoaxes in the Post-Truth era from an Islamic legal perspective. This study investigates the criteria by which news (al-khabar) is deemed true or false based on its source and transmitter. It highlights the importance of using qat‘i-zanni (definitive-presumptive) reasoning to assess the credibility of news sources and the quality of their transmitters as a procedure for analyzing the truthfulness of reported information. Through a combination of qualitative methods from Islamic legal literature and modern philosophy, the research finds that qat‘i-zanni reasoning can be used critically to determine the validity of information in the digital age. The conclusion suggests that all information shared in the Post-Truth era should be treated as presumptive, not definitive.